The comparison of aerodynamic and stability characteristics between conventional and blended wing body aircraft - Wang, Faliang (Cranfield University, 2012)
Aircraft with advanced wing geometry, like the flying wing or blended wing body configuration, seems to be the seed candidate of future aircraft. Compared with conventional aircraft, there are significant aerodynamic performance improvements because of its highly integrated wing and fuselage configuration. On the other hand, due to its tailless configuration, the stability characteristics are not as good as conventional aircraft. The research aims to compare the aerodynamic and stability characteristics of conventional, flying wing and blended wing body aircraft. Based on the same requirement—250 passenger capability and 7,500 nautical miles range, three different configurations—conventional, flying wing and blended wing body options were provided to make direct comparison. The research contains four parts. In the first part, the aerodynamic characteristics were compared using empirical equation ESDU datasheet and Vortex-Lattice Method based AVL software. In the second part, combined with the aerodynamic data and output mass data from other team member, the stability characteristics were analysed. The stability comparison contains longitudinal, lateral-directional static stability and dynamic stability. In the third part, several geometry parameters were varied to investigate the influence on the aerodynamic and stability characteristics of blended wing body configuration. In the last part, a special case has been explored in an attempt to improve the static stability by changing geometry parameters. The process shows that the design of blended wing body is really complex since the closely coupling of several parameters.
Keywords: ESDU; AVL; tailless configuration; geometry parameter; influence